Failing banks - Sergio Correia; Stephan Luck; Emil Verner (Federal Reserve Bank of New York, 2024)
Why do banks fail? We create a panel covering most commercial banks from 1865 through 2023 to study the history of failing banks in the United States. Failing banks are characterized by rising asset losses, deteriorating solvency, and an increasing reliance on expensive non-core funding. Commonalities across failing banks imply that failures are highly predictable using simple accounting metrics from publicly available financial statements. Predictability is high even in the absence of deposit insurance, when depositor runs were common. Bank-level fundamentals also forecast aggregate waves of bank failures during systemic banking crises. Altogether, our evidence suggests that the ultimate cause of bank failures and banking crises is almost always and everywhere a deterioration of bank fundamentals. Bank runs can be rejected as a plausible cause of failure for most failures in the history of the U.S. and are most commonly a consequence of imminent failure. Depositors tend to be slow to react to an increased risk of bank failure, even in the absence of deposit insurance.
Keywords: G01; G21; N20; N24; 330; bank runs; bank failures; financial